Police Department in the Kuznetsk, Barnaul, and Biysk Districts (Parishes) in the Second Half of the XIX Century - Yu. N. Moskvitin (Вестник Кемеровского государственного университета, 2020)
The research featured the changes associated with the abolition of serfdom, which affected the law enforcement system of the state and, most of all, the police. In Siberia, police reforms were conducted several years after they had been introduced in the Central European part of the state. While the reforming of the police system of the Tomsk province was inevitable, the process was especially difficult for three parishes (uyezds), namely, Kuznetsky, Barnaul, and Biysk. The problem was that on these territories there were eight mining areas, or volosts: two in Barnaul (Pavlovsk and Suzun), one in the Kuznetsk (Salair), and five in Biysk (Loktev, Kolyvansk, Riddersk, Zmeinogorsk, and Zyryanovsk). The abolishment of the mining police in the mining volosts predetermined some specifics of the local police forces. In the newly emerging conditions of interaction between the authorities of the Altai mining district and Tomsk, contradictions often arose on the issues of appointment to the posts of police officials in mining villages. Each institution wanted to gain control over the population of the volosts. When municipal and district (uyezd) police had to merge together under the command of the uniform police officer, this process was also extremely painful. In the post-reform period, the tsarist government sought to adapt existing rules to new conditions. As a result, provincial audits became one of the forms of control over the activities of police officers. However, the autocracy failed to start a comprehensive reform of the police in order to relieve the burden of extrinsic functions.